Performance analysis and evaluation of ethanol potential of Nzoia Sugar Company Ltd. - Moses Jeremiah Barasa Kabeyi; Oludolapo Akanni Olanrewaju (Energy Reports, 2022)
The Sugar industry faces several sustainability challenges due to dumping of excess global production which cause stiff competition for high cost sugar producers like Kenya. Through diversification into cogeneration and ethanol production, sugar companies in high cost producing countries can remain competitive and survive in the market. In this study, the technical and economic feasibility of ethanol production is done for the case of Nzoia Sugar Company in Kenya whose milling capacity is 3000 tons of cane per day (TCD). Molasses is taken through a series of stages starting with pretreatment, followed by fermentation and distillation to produce ethanol. The ethanol formed is then transferred to the distillation columns for fractionation to remove water and hence have ethanol rich product. Through further distillation and molecular sieve dehydration the purity and quality of the final ethanol product is enhanced. The main equipment for the process includes the fermenter, boilers, condensers, and distillation columns, design to suit the product characteristics and design capacity of the plant. The analysis showed that ethanol production by a 3000 TCD sugar factory is a profitable venture. The study showed that investment is both technically and economically feasible and will improve the financial performance and sustainability of the sugar factory in a competitive market environment. Therefore, diversification into ethanol production is an important strategy in sustaining the sugar industry in a competitive global market.